THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, PRICE, AND PROMOTION ON CONSUMER PURCHASING DECISIONS FOR COSMETIC PRODUCTS WARDAH IN MEDAN CITY - Gressella Anjelina simarmata; Yois Nelsari Malau; Graciella Novitasari Napitupulu; Niarita Bukit (Journal Accounting International Mount Hope, 2025)
This study examines how price, promotion, service quality, and product quality affect Wardah cosmetic purchases from Anggi Cosmetics Shop Medan. Wardah's Top Brand Index, which tracks blush-on product decline, was used. This index was 28.6% in 2021–2022 and 14.2% in 2023. A quantitative data set was created by randomly selecting 67 clients out of 100 to complete a questionnaire. Women over 18 who used Wardah products can participate. Multiple linear regression and classical assumption testing data analysis. Four independent variables explained 69.8% of consumer purchases, while extraneous factors explained 30.2%.